Changes in behavioral and neuronal parameters by alcohol, cigarette, or their combined use in rats. Issue 6 (September 2019) - Bandiera, Solange; Caletti, Greice; Giustina, Clara L.D.; Hansen, Alana W.; Deniz, Bruna F.; Confortim, Heloisa D.; Pulcinelli, Rianne R.; Nin, Mauricio S.; Silva, Lenir O.P.; Gomez, Rosane
Abstract : Few studies have explored the effects of the combined use of alcohol and cigarette in humans, despite its prevalence. Here we evaluated the effect of isolated and combined use on behaviors and neuronal parameters in rats. Male adult rats were divided into alcohol (AL, 2 g/kg, by oral gavage), cigarette smoke (TB, six cigarettes, by inhalation), combined use (ALTB), or control (CT, water by oral gavage and environmental air) groups, treated twice a day (09.00 and 14.00 h). After 4 weeks, the rats were tested in the open field for behavioral analysis and euthanized for brain volume estimation and counting of neurons in the hippocampus. All treatments increased locomotion, and this behavior was higher in the ALTB than TB group. Latency to exit from the central area was lower in the ALTB than in the AL or CT groups. Rearing behavior increased in TB and decreased in AL and ALTB rats. Combined ALTB rats significantly increased their grooming behavior. Only the AL group showed decreased neuron counts and increased brain volume. Our results show that the isolated and combined uses of alcohol and cigarette smoke have diverse effects on behavioral and neuronal parameters in rats after long-term treatment.